THE MULTICULTURAL EDUCATION IN THE WALISONGO MODERN ISLAMIC BOARDING SCHOOL (PESANTREN MODERN) - El-Rumi, Umiarso (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
A new phenomenon emerged in Walisongo modern Islamic Boarding School (pesantren modern), namely the process of integration of multicultural Islamic education values. Its become more established and plays more functions in the context of a global society. This paper focuses on the concept of multicultural education developed and implemented in the learning process of Walisongo modern pesantren. This paper employed a qualitative approach using a phenomenological type of research, and the technique of purposive and snowball samplings in gaining the data. Spradley model was applied to analyze the data; whereas the triangulation strategy and member check were implemented to gain data validity. This study concludes, the formation of the multicultural characters of santri uses the approach of integrating philosophical, spiritual, psycho-philosophical, and socio religious-philosophical values.